Characterization of odour-active volatiles and sensory analyses of roasted oak (Quercus humboldtii Bonpl.) acorns, a coffee substitute - DÍAZ-ROJAS, Liseth; GALÁN-BERNAL, Nathaly; FORERO, Diana Paola; LINARES, Edgar Leonardo; MARÍN-LOAIZA, Juan Camilo; OSORIO, Coralia (Vitae, 2019)
Background: Oak acorns are roasted and grounded to produce a powder that is used to prepare a coffee substitute beverage. Objective: To identify the odour-active volatiles of the powder derived from roasted acorns of Quercus humboldtii and to perform a quantitative descriptive analysis (QDA) of its appearance, odour, and taste. Methods: The odour-active volatiles of roasted oak acorn powder were extracted by SDE and analyzed by GC/MS and olfactory analyses (GC/O). Sensorial analyses of this beverage were done by QDA (Quantitative Descriptive Analysis). Results: Nineteen compounds were identified, showing acid, buttery/caramel, smoke/roasted, and fruity odour notes, which are common to those of roasted coffee. Ketones, aldehydes, aliphatic acids, furanic alcohols and pyrazines were identified as relevant for this coffee substitute beverage. The major volatile compounds were furfural, 5-methyl furfural, furfuryl alcohol, and 3-hydroxy-2-butanone, some of them related to the sugar breakdown by heating. Odour attributes characterized by QDA, were in agreement with those detected by GC-O (Gas Chromatography coupled to Olfactometry), but some off-taste notes were detected. Conclusions: The results of molecular sensory approach confirmed that this product resembles coffee; however, QDA analyses showed the presence of undesirable taste. More studies are needed in order to improve the taste quality of this coffee substitute.